Pengaruh Media Audio Visual Edukasi Smart (AVES) Terhadap Hasil Belajar Keterampilan Dasar Praktik Mahasiswa Kebidanan - Herni Johan; Siti Noorbaya; Siti Saidah (Indonesian Journal of Midwifery (IJM), 2021)
Research on the Effect of Smart Educational Audio Visual Media (AVES) on Learning Outcomes of Basic Practice Skills for Midwifery Students, is a research on the development of teaching media designed to be the main supporting tool for learning basic midwifery practice in practicing clinical skills and improving student learning outcomes. Midwifery program education requires graduates to be skilled in carrying out their professional duties as skilled midwives and declared competent after they pass the national competency exam. The purpose of this study was to determine the effect of smart educational audio visual media (AVES) on learning outcomes of students' basic skills in midwifery practice. This research method uses an experimental method with the research design that will be used is a pre-experimental design type one group pretest-posttest design. The population in this study were all 87 students of midwifery class XIII and XIV. The sampling technique is non-probability sampling with a purposive sampling model, as many as 28 students. The results of this study are that the data obtained, that tcount = 2.310 > ttable = 2.0555 with a significance of 0.029 <0.05, then H0 is rejected and H1 is accepted. the researchers can conclude that there is a positive and significant influence between Smart Audio Visual Education Media on Learning Outcomes of Basic Skills Practice of Midwifery Students